If you complete the square on the equation

x^2 + 10x = 9 + 4x,

you will get an equation of the form "(x + r)^2 = c". Enter this equation.

Guest May 23, 2022

#1**+1 **

We first move all terms to the left-hand side.

\(x^2 + 10x - 4x - 9= 0 \\ x^2 + 6x - 9= 0\)

We want to make (x + r)^2 on the left-hand side, and we know that (x + 3)^2 = x^2 + 6x + 9. What if we add 18 to both sides?

\(x^2 + 6x + 9 = 18\)

Now just write the left-hand side as (x + 3)^2 and there's the answer.

MaxWong May 23, 2022